Exhumation history and Early Cretaceous paleogeography of the Newfoundland margin revealed by detrital zircon U–Pb and fission-track studies of syn-rift Hibernia Formation strata. (February 2023) - Johns-Buss, Emily G.; Beranek, Luke P.; Enkelmann, Eva; Jess, Scott; Matthews, William
Abstract: Syn-rift strata in the Grand Banks of Atlantic Canada are the result of Late Triassic to Cretaceous extensional processes within the proximal domain of the Newfoundland margin. The precise timing of exhumation events in proximal domains and their significance to the stepwise, long-term development of magma-poor rift systems globally remains uncertain. We report new detrital zircon U–Pb ( n = 518) and double-dating fission-track (FT) and U–Pb ( n = 269) results from seven samples of syn-rift, Lower Cretaceous Hibernia Formation sandstone units from the Jeanne d'Arc basin to constrain the timing of proximal domain rift processes in the Grand Banks during the onset of hyperextension and outboard development of the necking and distal domains. Syn-depositional, Early Cretaceous U–Pb detrital zircon dates for Berriasian to Barremian strata of the Hibernia Formation indicate provenance from volcanic centers along the SW Grand Banks transform and are consistent with north-directed paleoflow into the southern Jeanne d'Arc basin. Hibernia Formation strata mostly yield Neoarchean to Paleozoic detrital zircon grains with Cryogenian to Paleozoic FT cooling populations that document the episodic exhumation of Appalachian basement and cover successions. The near-zero lag time between the ages of Early Cretaceous exhumation-related cooling and Berriasian to Barremian deposition are consistent with rapid exhumation along NNE-trending normal fault systems in the Avalon Uplift region and margins of the Jeanne d'Arc basin. Early Cretaceous FT cooling populations in Hibernia Formation strata support this rapid tectonic exhumation being coincident with the onset of hyperextension and mantle exhumation processes outboard of the Grand Banks and crustal breakup along SW Iberia that are more generally constrained by marine geophysical studies. Syn-rift strata in long-lived, proximal domain basins can therefore test the timing of exhumation processes that result from magma-poor rift development, including lithospheric thinning associated with the generation of outboard architectural elements. Highlights: Syn-rift strata record exhumation of proximal domain rocks in magma-poor systems. Exhumation-related cooling resulted from proximal, necking, and distal domain growth. Cretaceous zircons were sourced from igneous rocks near SW Grand Banks transform. Near-zero lag time between cooling and deposition indicates rapid exhumation. Some Paleozoic and older zircons yield inherited cooling ages that pre-date rifting.